Changes in Problem-Solving Capacity and Association With Spontaneous Brain Activity After a Single Electroconvulsive Treatment in Major Depressive Disorder. Issue 1 (March 2016) - Du, Lian; Qiu, Haitang; Liu, Haixia; Zhao, Wenjing; Tang, Yong; Fu, Yixiao; Li, Xirong; Qiu, Tian; Hu, Hua; Meng, Huaqing; Luo, Qinghua
Abstract : Background: Modified electroconvulsive therapy (MECT) has been regarded as the most effective antidepressant therapy, despite its cognitive side effects. However, how MECT influences problem-solving capacity in major depressive disorder (MDD), as well as its underlying neurobiological mechanisms, remains unclear. The present study aimed to assess alterations in problem-solving capacity after MECT and to explore spontaneous brain activity using amplitudes of low-frequency fluctuations (ALFF)/fractional ALFF. Methods: Thirteen first-episode, treatment-naive MDD patients treated by MECT were recruited. We collected resting-state functional magnetic resonance imaging, and we evaluated their Modified Card Sorting Test performance before and after single-session MECT. Another 11 MDD patients without MECT were also recruited and interviewed with Modified Card Sorting Test twice as a control group. Results: After a single MECT, MDD patients showed significantly decreased ALFF in the right cerebellar posterior lobe. Compared to the control group, perseverative errors significantly decreased after MECT, controlling for practice effects. Some cognitive functional changes significantly correlated to changed ALFF in several brain regions, including Brodmann areas BA9, BA19, BA 21, and BA48, right thalamus, left cerebellum, and right postcentral gyrus. Conclusions: The MECT could improve problem-solving capacity, even after controlling for practice effects, and it could induce changes in spontaneous brain activity. These changes in cognitive functioning might result from changes in the cerebral functions of some regions, including frontal cortex, a key region for problem-solving capacity.